Entertainment Satisfaction and Critical Attitudes of West Java Students on 2024 Presidential Election News - Dafina Shafa Salsabil; Kunto Adi Wibowo (Insan Akademika Publications, 2025)
In today's digital age, social interaction is heavily influenced by social media as the primary source of information. Social media provides an easy and economical user experience, but it also increases the potential of spreading misinformation. Twitter, which has 60.2% of Indonesian users, serve as the focal point for analyzing misinformation during Indonesia's 2024 presidential election. This research focuses on examining Twitter as a platform for the relationship between several entertainment-driven objectives and sharing false election-related news among users during Indonesia’s 2024 presidential election. Data from 229 university students in West Java were collected and analyzed using a quantitative approach and survey method. The study revealed a significant positive correlation (r =.477, p <.001) between entertainment enjoyment and spreading false election-related news. Respondents were found to share content they perceived as entertaining, even when it turned out to be incorrect, for reasons such as comedy (M = 2.83, SD = 1.362) and enjoyment (M = 2.98, SD = 1.291). The study confirmed the hypothesis that entertainment satisfaction drives the spread of misinformation (t = 8.186, p <.001). These findings highlight the influence of entertainment-driven motivations in spreading misinformation and emphasize the importance of reducing such behavior. This study proposes insights for policymakers and social media platforms into addressing the complex nature of information-sharing behavior in the digital world. Further psychological and contextual factors impacting the spread of fake news dissemination across various demographic groups should be explored in future studies